2021
DOI: 10.1016/j.cej.2021.129565
|View full text |Cite
|
Sign up to set email alerts
|

Improved value and carbon footprint by complete utilization of corncob lignocellulose

Abstract: Lignocellulose, as the most abundant type of inedible biomass, is considered as a promising renewable feedstock for making fuels, chemicals, and materials. However, its complex structure makes most of current biorefinery processes suffer from low resource utilization rates, high energy consumption or ill-defined market orientation of the obtained products. Here, we propose and evaluate the EXA (Ethanol, Xylose, Adhesive) biorefinery strategy based on current xylose industry. This process integrates four conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 62 publications
(77 reference statements)
0
21
0
Order By: Relevance
“…These results and analyses suggest that the ETS strategy is suitable for the fermentation using lignin as a sole carbon source. Lignocellulosic biorefinery presents a sustainable and promising route for the manufacturing of biofuels and chemicals. , An important target of biorefinery is to fractionate the major components of lignocellulosic biomass (e.g., cellulose, lignin, and hemicellulose) into distinct streams so that they can be independently processed with highly selective biological or catalytic systems. , With various pretreatment methods, such as organic solvents, , deep eutectic solvents, and ionic liquids, lignin can be isolated and recovered effectively. With high purity, lignins originating from such biorefinery scenarios are also considered as suitable substrates for the ETS strategy.…”
Section: Resultsmentioning
confidence: 99%
“…These results and analyses suggest that the ETS strategy is suitable for the fermentation using lignin as a sole carbon source. Lignocellulosic biorefinery presents a sustainable and promising route for the manufacturing of biofuels and chemicals. , An important target of biorefinery is to fractionate the major components of lignocellulosic biomass (e.g., cellulose, lignin, and hemicellulose) into distinct streams so that they can be independently processed with highly selective biological or catalytic systems. , With various pretreatment methods, such as organic solvents, , deep eutectic solvents, and ionic liquids, lignin can be isolated and recovered effectively. With high purity, lignins originating from such biorefinery scenarios are also considered as suitable substrates for the ETS strategy.…”
Section: Resultsmentioning
confidence: 99%
“…It can thus be concluded that the strategy of coupling carbon microspheres and Fe, N co-doped redox active sites endows the material with high capacitance and good rate capability. It is well known that the cycling stability is of vital importance in energy storage devices, therefore, the long-term working lifespan of S1 † for references: [1] wheat straw; [2] sawdust; [3] bamboo chips; [4] lignocellulose; [5] cotton; [6] hemp stem; [7] bamboo; [8] larch sawdust; [9] rice straw; [10]…”
Section: Electrochemical Performance Of Fe-n-c Assembled Supercapacitorsmentioning
confidence: 99%
“…Moreover, current industrial technologies involving lignocellulose valorization are fully focused on carbohydrate translation in paper making and bioethanol, which severely suppresses their overall functional diversity. 4 With its unique hierarchical structure, ability to act as a chemical-energy reservoir, and capability of CO 2 fixation and ion/water transportation, lignocellulose is a common candidate that can impart both energy attributes and water purification into traditional biorefining platforms. 5 In this regard, the expansion of multifaceted and cost-competitive lignocellulose valorization covering a product portfolio that aligns with the requirements of the petroleum equivalents is a highly important issue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations